The Evolution of Diagenetic Fluids and Accumulation Characteristics of Tight Sandstone Reservoir in Upper Paleozoic, Southwestern Ordos Basin. (15th June 2021) - Zhu, Ruijing; Li, Rongxi; Wu, Xiaoli; Qin, Xiaoli; Zhao, Bangsheng; Liu, Futian
Abstract : The Upper Paleozoic in the southwestern Ordos Basin has significant potential for natural gas exploration. This study investigated the diagenetic fluid evolution and hydrocarbon accumulation characteristics of He 8 section from Permian Lower Shihezi formation and Shan 1 section from Shanxi formation tight sandstone reservoirs by petrographic observation, scanning electron microscope imaging, fluid inclusion study, and laser Raman spectrum analysis. The results show that He 8 section and Shan 1 section reservoirs are mainly composed of quartz sandstone, subordinate arkose quartz sandstone, and lithic quartz sandstone, with minor lithic sandstone and lithic arkose sandstone. The major pores are intergranular dissolved pores. The main diagenetic minerals include quartz overgrowth, siliceous cement, carbonate cement, illite, montmorillonite, and mixed-layer clay minerals. The overall diagenetic features show strong compaction, multistage siliceous and calcareous cements, and abundant clay minerals, strong dissolution, and well-developed fractures. Two stages of fluid inclusions developed in the He 8 and Shan 1 sections recorded the migration and accumulation of the early-stage and late-stage natural gas, respectively. The reservoir in the study area experienced early and late diagenetic stages, and its formation was simultaneous with or after its densification. The diagenetic environment changed from alkaline to acidic and again into alkaline. There are two stages of fluid activities in the study area, namely, the early diagenetic stage corresponding to hydrocarbon generation and migration and the late diagenetic stage corresponding to hydrocarbon accumulation. This study suggests that Upper Paleozoic natural gas migrated into the reservoir in Weibei Uplift, Yishan Slope, and Tianhuan Depression tectonic units during 220-197 Ma, and the large-scale migration and accumulation occurred in these tectonic units at different times. No natural gas was generated in the west margin of the basin because the temperatures of the hydrocarbon source rocks in the Upper Paleozoic were below the gas window.